Competing water uses between agriculture and energy: Quantifying future climate change impacts for the Portuguese power sector. (15th October 2022) - Fortes, Patricia; Simoes, Sofia G.; Armada Brás, Teresa; Amorim, Filipa
Abstract: Climate change may increase water needs for irrigation in southern Europe competing with other water uses, such as hydropower, which may likely be impacted by lower precipitation. Climate change will also potentially affect the variability and availability of other renewable energy resources (solar and wind) and electricity consumption patterns. This work quantifies the effect of competition for water use between irrigation and hydropower in the future 2050 Portuguese carbon-neutral power sector and under Representative Concentration Pathway 8.5 climate change projections. It uses the power system eTIMES_PT model to assess the combined effects of climate change on the cost-optimal configuration of the power sectorconsidering changes in irrigation, hydropower, wind and solar PV availability. eTIMES_PT is a linear optimisation model that satisfies electricity demand at minimal total power system cost. Results show that, by 2050, climate change can lead to an increase in annual irrigation water needs up to 12% in Tagus and 19% in Douro watersheds (from 2005 values), with substantially higher values for spring (up to 84%). Combining these increased water needs with the expected reduction in river runoff can lead to a decline in summer and spring hydropower capacity factors from half to three times below current values. By 2050, concurrent water uses under climate change can reduce hydropower generation by 26–56% less than historically observed, mainly in summer and spring. Higher solar PV, complemented with batteries' electricity storage, can offset the lower hydropower availability, but this will lead to higher electricity prices. Adequate transboundary water management agreements and reducing water losses in irrigation systems will play a key role in mitigating climate impacts in both agriculture and power sector.